Individual Tree Parameters Models for Melia Azedarach (Chinaberry) Tree Grown in Erbil - Dahir, Srud Zubair; Salih, Tariq (Science Journal of University of Zakho, 2022)
The crown width of a tree is very important parameter. It is responsible for tree survival and for producing the food for the whole tree. They produce oxygen, filter out dust and other airborne pollutants from the air, purification of the water, generate shadow and determine the scenic beauty of trees and forests. The tree crowns have a significant effect on the microclimate. But measuring of the crown width is a difficult task that needs much money, time and effort. Thus this study aimed at developing of mathematical relationship between the crown width and breast height diameter for Chinaberry trees grown in Sami Abdulrahman Park in Erbil, Iraq. Both crown width and breast height diameters are the most important parameters of a tree. The breast height diameter of a tree can be measured very easily using diameter tape or caliper, unlike measuring of the crown width which is more cumbersome. Therefore, it is accustomed to regress it with breast height diameter in mathematical equations.to be used for prediction of crown width instead of measuring it whenever it is needed. Such regression models were undergone many measures of precision in order to select the most appropriate one that best fits the collected dataset. In this study 50 regression models were developed, of which 25 included the y- intercept and the other 25 regression models was without Y-intercept. The first group of regression models were excluded from the competition list because of having low values of the coefficient of determination. The second group of equations were subjected to many criteria for the purpose of selecting the best one and at last the equation: was finally selected for its high prediction ability and simplicity in application. According to this equation the crown width of for Chinaberry trees grown in (Sami Abdulrahman Park in Erbil) increases with 1.50168m for each unit increase in <img src="data:image/png;base64,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" width="12" height="12" /> .